Total Consumer Exposure to Polybrominated Diphenyl Ethers in North America and Europe - Trudel, David; Scheringer, Martin; von Goetz, Natalie; Hungerbühler, Konrad (Environmental science & technology, 2011)
Polybrominated diphenyl ethers (PBDEs) have been widely used as flame retardants in textiles, polyurethane foams, and plastics. PBDEs exert toxic effects in various organisms, including humans, and are ubiquitous in the outdoor and indoor environment. Here we estimate total daily PBDE doses received by consumers in North America and Europe, along with the most important pathways and congeners, and derive PBDE elimination half-lives for chronic exposure. We estimate distributions for all parameters (PBDE concentrations in exposure media, food consumption rates, etc.) and conduct a probabilistic exposure assessment. We find that Americans are exposed the most, likely due to stricter fire regulations, followed by consumers from the UK and Continental Europe. In the central quantiles of the exposure distributions derived, food is the dominant pathway; in the upper quantiles either food or oral and dermal exposure to dust. This reflects the lipophilic and persistent nature of PBDEs and their use in products for indoor-use. Median elimination half-lives are in a range of 1−3 years except for BDE-153 with about seven years and BDE-209 with 4−7 days.